Cell therapy in muscular dystrophies: many promises in mice and dogs, few facts in patients. (September 2015) - Skuk, Daniel; Tremblay, Jacques P
<x xml:space="preserve">Abstract</x> Introduction: Muscular dystrophies (MDs) are genetic diseases that produce progressive loss of skeletal muscle fibers. Cell therapy (CT) is an experimental approach to treat MD. The first clinical trials of CT in MD conducted in the 1990s were based on myoblast transplantation (MT). Since they did not yield the expected results, several researchers sought to discover other cells with more advantageous properties than myoblasts whereas others sought to improve MT. Areas covered: We explain the properties that are required for a cell to be used in CT of MD. We briefly review most of the cells that were proposed for this CT, and to what extent these properties were met not only in laboratory animals but also in clinical trials. Expert opinion: Although the repertoire of cells proposed for CT of MD has been expanded since the 1990s, only myoblasts have currently demonstrated unequivocally to significantly engraft in humans. Indeed, MT for MD involves significant technical challenges that need be solved. While it would be ideal to find cells involving less technical challenges for CT of MD, there is so far no clinical evidence that this is possible and therefore the work to improve MT should continue.